Rare earth element (REE) lanthanum doped zinc oxide (La: ZnO) nanomaterials: synthesis structural optical and antibacterial studies - Manikandan, A.; Manikandan, E.; Meenatchi, B.; Vadivel, S.; Jaganathan, S.K.; Ladchumananandasivam, R.; Henini, M.; Maaza, M.; Aanand, Jagathrakshakan Sundeep (Elsevier, 2017)
Lanthanum (La) doped zinc oxide (ZnO) nanomaterials (LaxZn1-xO, x = 0.0, 0.03, 0.05, 0.07 M) were synthesized via co-precipitation method using zinc acetate, lanthanum nitrate as precursors, octylamine as capping and reducing agent. The structures, morphologies, optical activity and antibacterial properties of LaxZn1-xO were investigated by powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, High resolution scanning electron microscopy (HR-SEM), Energy dispersive X-ray (EDX), UV–Visible, Photoluminescence (PL) spectroscopy. The antibacterial activities of LaxZn1-xO were tested by modified disc diffusion method. The XRD results showed that the La3+ ions were successfully incorporated into the ZnO host, and the products were well-crystalline. The average size of undoped and doped La-doped ZnO was found to be in the ranges from 15.64 to 10.18 nm. In addition, the sphere-like nanoparticles morphology of LaxZn1-xO was confirmed by HR-SEM images. The band gap of La-doped ZnO nanoparticles were varied with the La3+ ions doping concentration. In addition, increasing the doping concentration of La3+ ions in ZnO increases the defects in ZnO lattice and hence resulting red-shift in UV emission, which indicate the presence of narrow band-gap in doped nanoparticles.